Effect of different concentrations of BAP and kinetin on polyembryony induction of Mangifera indica L. seeds - Ahmad Azmi, Mohamad Nazrin (2013)
An experiment was conducted to study the effect of different concentrations of BAP and Kinetin on polyembryony induction of mango seeds. The experiment was carried at the In-vitro Laboratory at the Department of Agriculture Technology, Faculty of Agriculture UPM. Nine treatments were used which are 0 (the control treatment), 2, 4, 6 and 8 mg/L of BAP and kinetin respectively. Experimental design for this experiment was randomized complete block design (RCBD) with 9 treatments and 10 replications for each treatment. Seeds obtained were soaked in BAP and kinetin solution at different concentration for 1 hour and 30 minutes before sown into the perlite media. Data collection were made after 8 weeks based on the percentage of seeds inducing polyembryony per treatment and mean no of seedlings emerged per seed per treatment. It was observed that 6 mg/L BAP resulted in the highest percentage of seeds inducing polyembryony. However there is no significant difference between the range of concentration of BAP and Kinetin tested compared with the control treatment in enhancing shoot induction per seeds of mango.